Providing a Sure Start : How government discovered early childhood - Eisenstadt, Naomi (Book collections on Project MUSE., 2011)
Offering insight into the key debates on services for young children, this book tells how Sure Start was set up, the numerous changes it went through, and how it has changed the landscape of services for all young children in England.